2017
DOI: 10.12669/pjms.336.13812
|View full text |Cite
|
Sign up to set email alerts
|

CNS relapse of diffuse large B cell Lymphoma: A single centre experience

Abstract: Background and Objective:Central nervous system (CNS) relapse of diffuse large B cell lymphoma (DLBCL) is relatively uncommon and nearly fatal. Two years CNS relapse risk is 0.8% in low, 3.9% in intermediate and 12% in high risk patients. Our aim was to study, the baseline characteristics and outcome in term of median survival of DLBCL patients with CNS relapse.Methods:This is a retrospective analysis. All patients of DLBCL with CNS relapse from 2006 to 2014 were included. Data were collected from computerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Similar risk factors were reported by the UK NCRI R-CHOP-14 vs. 21 trial, where a performance status of 2, elevated lactate dehydrogenase level, IPI, >1 extranodal site of disease and the presence of a 'high-risk' extranodal site were significant risk factors for CNS relapses (17). In the study by Nazir et al (30), an advanced stage, high LDH level and extranodal involvement at the first presentation were significant risk factors for CNS relapse.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar risk factors were reported by the UK NCRI R-CHOP-14 vs. 21 trial, where a performance status of 2, elevated lactate dehydrogenase level, IPI, >1 extranodal site of disease and the presence of a 'high-risk' extranodal site were significant risk factors for CNS relapses (17). In the study by Nazir et al (30), an advanced stage, high LDH level and extranodal involvement at the first presentation were significant risk factors for CNS relapse.…”
Section: Discussionsupporting
confidence: 71%
“…The study found that intrathecal MTX was not optimal for CNS prophylaxis, since CNS relapses occurred in 4 patients, with a 2-year cumulative incidence rate of CNS relapse of 12.5%. In another single-center retrospective study of 21 patients with DLBCL who received CNS prophylaxis by intrathecal and intravenous MTX, half of the patients had CNS relapses, with a poor prognosis and a median survival time of 54 days (30).…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 21 , 22 In terms of DLBCL, elevated LDH level at initial diagnosis was found to be related to the increased risks of CNS relapse. 23 , 24 Compared with patients with late relapses, patients with early relapses were more likely to have a higher LDH level, higher IPI score and adverse stage (III–IV). 25 In Huang’s study, univariate analysis also indicated that LDH >1000U/L was one of the relapse risk factors of pediatric mature B cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%